Implementasi e-Government dalam Pelayanan Tol di Indonesia - Harahap, Insan Harapan (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
Abstract - PT Jasa Marga has utilized the development of information technology by applying the principles of e-government through e-toll services. Provision of non-cash toll tariff payment transaction services has been implemented simultaneously starting October 31, 2017. The toll payment transaction process has changed from manual to e-toll. The implementation of e-toll services aims to improve transaction services at toll gates in a good and optimal way. It is hoped that e-toll services can realize transparency, efficiency, effectiveness, safety and comfort for toll road users. E-toll is considered to be able to provide service time benefits for consumers. Toll road users or drivers do not need to have to pay toll tariff transactions for a long time. Only by attaching the e-toll card to the reader machine that is available at the Automatic Toll Gate (GTO), users can enter the toll road. The e-toll implementation also has the potential to reduce and overcome congestion due to long queues at toll gates. But in its implementation, e-toll also still has some shortcomings that must be addressed. For example, the e-toll card reader machine is damaged or slow reading e-toll cards, it is difficult to refill e-toll balances, the balance is cut twice, the availability of refill places, and there is a balance limit on e-toll cards. In addition, the implementation of e-toll has a long-term congestion effect due to damaged or malfunctioning reader machines and the potential for employee reductions, which have been serving at the toll gate. Keywords: e-government, public services, e-toll, and e-toll cards.   Abstrak - PT Jasa Marga telah memanfaatkan perkembangan teknologi informasi dengan menerapkan prinsip e-government melalui layanan e-toll. Penyediaan atas layanan transaksi pembayaran tarif tol nontunai sudah diimplementasikan secara serentak mulai 31 Oktober 2017. Proses transaksi pembayaran tol berubah dari manual menjadi e-toll. Implementasi layanan e-toll bertujuan untuk meningkatkan pelayanan transaksi di gerbang tol secara baik dan optimal. Diharapkan layanan e-toll bisa mewujudkan transparansi, efisien, efektif, aman, dan nyaman bagi para pengguna jalan tol. E-toll dinilai dapat memberikan keuntungan waktu pelayanan bagi konsumen. Para pengguna jalan tol atau pengendara tidak perlu harus melakukan transaksi pembayaran tarif tol dengan waktu yang lama. Hanya dengan menempelkan e-toll card pada mesin reader yang sudah tersedia di Gerbang Tol Otomatis (GTO), pengguna sudah bisa memasuki tol. Implementasi e-toll juga berpotensi mengurangi dan mengatasi kemacetan akibat antrian yang panjang di gerbang tol. Namun dalam implementasinya, e-toll juga masih memiliki beberapa kekurangan yang harus dibenahi. Misalnya, mesin reader e-toll card rusak atau lambat membaca e-toll card, susah melakukan isi ulang saldo e-toll, saldo terpotong dua kali, ketersediaan tempat isi ulang, dan adanya limit saldo pada e-toll card. Selan itu, implementasi e-toll memiliki dampak kemacetan yang panjang akibat mesin reader rusak atau tidak berfungsi dan potensi pengurangan karyawan (PHK) yang selama ini bertugas di gerbang tol. Kata kunci: e-government, layanan publik, e-toll, dan e-toll card.